Prevalence and Correlates of Self-Handicapping Tendencies among Physical Education Preservice Teachers - Seidu Sofo; Adolfo Ramos; Emmanuel Thompson; Sara Garner (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The study examined the prevalence and correlates of self-handicapping tendencies among physical education preservice teachers from one university. The participants were a purposive sample of physical education preservice teachers (67% male and 33% female) from one university in  midwestern United States. An adapted version of the short version of the Self-Handicapping Scale (SHS) served as the data source. The SHS score served as the response variable. The predictor variables were gender, the number of credit hours attempted, the number of credit hours passed, the Cumulative Grade Point Average (GPA), and GPA in the physical education content area. Results showed that 11.11% of the participants reported high levels of self-handicapping tendencies. The SHS had significantly low negative correlations with two predictors: the number of credit hours attempted and the number of credit hours passed. Conversely, SHS showed moderate significant positive correlations with cumulative GPA and the GPA in the physical education content area. The SHS scores for males and females were similar.Teacher education programs can help future teachers adopt coping strategies, thereby reducing their tendency to engage in self-handicapping strategies